NGOs and donors' funding: Evidence from Uganda - Spiros P. Bougheas; Alessia Isopi; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2022)
We develop a screening model to analyse the funding allocation criteria of institutional donors towards NGOs. The model shows that when donors care about efficiency, they screen NGOs and concentrate their funding on those that comply. Combining two waves, 2002 and 2008, of a unique survey data set of 412 NGOs in Uganda we show that local donors do not implement efficiency selectivity criteria but focus on the geographic location of the NGO and the manager's network. International donors, instead, follow efficiency proxies of both the NGO and the manager, including the manager's level of education, the appointment procedure, and external feedback on community needs. From focus group interviews with beneficiaries it appears they too reward efficiency proxies and show a higher appreciation for those NGOs funded predominantly by international donors.
Keywords: F35; D82; 330; Foreign Aid; Funding Allocation; NGO